Osteogenesis Imperfecta: A study of the patient journey in 13 European countries - Ingunn Westerheim; Valerie Cormier-Daire; Scott Gilbert; Sean O’Malley; Richard Keen (Orphanet Journal of Rare Diseases, 2024)
Abstract Introduction Osteogenesis imperfecta (OI) is a heritable skeletal disorder and comprises various subtypes that differ in clinical presentation, with Type I considered the least severe and Types III/IV the most severe forms. The study aim was to understand the OI patient diagnostic and treatment journey across Europe. Methods We conducted a qualitative, descriptive study to understand the OI patient journey. A selection of people with OI/their caregivers and clinicians involved in OI-patient care from across Europe were interviewed using a specially developed questionnaire. Results Between May 2022 and July 2022, 22 people with OI/caregivers and 22 clinicians (endocrinologists, orthopaedic surgeons, geneticists and metabolic specialists) from across Europe were interviewed. Our study showed various areas of concerns for the OI community. Timely diagnosis of OI is essential; misdiagnoses and a delay to treatment initiation are all too common. There are a lack of consensus guidelines regarding optimal treatments (including when bisphosphonate therapy should be initiated and the route of administration) and patient management throughout the duration of the patient’s life. Adult OI patients do not have a medical home and are often managed by endocrinologists and rheumatologists. Adult care is often reactive based on the development of new symptoms. The psychosocial burden of OI impacts on the patient’s quality of life. Conclusions There is an urgent need for increased awareness about OI and its wide range of symptoms. In particular, there is a need for consensus guidelines outlining the optimum care throughout the duration of the OI patient’s life.